Sintesis 1-(4-metoksibenzoiloksimetil)-5-fluorourasil sebagai Agen Antikanker - . Ifada; Ayik Rosita Puspaningtyas1; Ika Oktavianawati; Yuni Retnaningtyas; Nia Kristiningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2013)
A new compound from 5-fluorouracil (5-FU) derivatives, 1-(4-methoxybenzoyloxymethyl)-5-fluorouracil has been synthesized in a two steps reaction, alkylation (5-FU and formaldehyde to form 1-hydroxymethyl-5-fluorouracil) and esterification (1-hydroxymethyl-5-fluorouracil and 4-methoxybenzoylchloride to form 1-(4-methoxybenzoyloxymethyl)-5-fluorouracil). Reaction product purified by chromatography column, the product has been characteryzed for physical apperance is a yellowish white, crystal and melting range 168-169OC. Based on the FTIR and 1H-NMR spectra, it showed that the purified product does not contain a single compound. This fact is supported by Thin Layer Chromatography (TLC) result showing two spots for the pressure of 1-(4-methoxybenzoyloxymethyl)-5-fluorouracil and 4-methoxybenzoate acid. Keywords: 5-fluorouracil derivates, anticancer, 1-(4-methoxybenzoyloxymethyl)-5-fluorouracil, benzoylation.